Report on the activities of the the Latin American and Caribbean Institute for Economic and Social Planning (ILPES), 2008-2013 : strengthening capacities in public administration and planning for development with equality in Latin America and the Caribbean (ECLAC SantiagoCL, 2013)
Outlines the main activities carried out in the period 2008-2013, in accordance with the work programme adopted at the thirteenth meeting of CRP in 2007 and with the programmes of work of ECLAC which include the activities of ILPES.
Keywords: DEVELOPMENT PLANNING